Representasi Kuasa dalam Bingkai Visual Berita Bencana Alam di Televisi Indonesia: Kajian Semiotika Roland Barthes - Intan Novanaya; Rona Marina Nisaasari; Edison Bonar Tua Hutapea (Institut Nalanda, 2026)
This study examines the representation of power embedded in the visual framing of natural disaster news on Indonesian television. Natural disasters, as events frequently exploited visually, serve as arenas in which power is produced and represented through seemingly neutral visual signs. Drawing on Roland Barthes' semiotic framework encompassing denotation, connotation, and myth, this study analyzes 24 news clips from two national television stations, Metro TV and Trans 7, covering the 2023 Jakarta floods and the 2022 Cianjur earthquake. The findings reveal that television news coverage consistently positions authority figures such as government officials, disaster management agency heads, and military personnel in visually dominant positions. This visual pattern constructs a myth that the state is the principal actor capable of and authorized to manage disaster situations. The study argues that the visual framing of disaster news does not merely document events but actively constructs power hierarchies while marginalizing victims as passive subjects.